2009
DOI: 10.1371/journal.pone.0006318
|View full text |Cite
|
Sign up to set email alerts
|

Self-Contained Induction of Neurons from Human Embryonic Stem Cells

Abstract: BackgroundNeurons and glial cells can be efficiently induced from mouse embryonic stem (ES) cells in a conditioned medium collected from rat primary-cultured astrocytes (P-ACM). However, the use of rodent primary cells for clinical applications may be hampered by limited supply and risk of contamination with xeno-proteins.Methodology/Principal FindingsWe have developed an alternative method for unimpeded production of human neurons under xeno-free conditions. Initially, neural stem cells in sphere-like cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The neural stem sphere (NSS) method is a simple neural differentiation method using only astrocyte-conditioned medium (ACM) prepared from serum-free medium under free floating conditions [40][41][42] . In brief, ES cell colonies formed on MEF feeder layers at clonal density are mechanically picked.…”
Section: Differentiation Of Es Cells By the Neural Stem Sphere Methodsmentioning
confidence: 99%
“…The neural stem sphere (NSS) method is a simple neural differentiation method using only astrocyte-conditioned medium (ACM) prepared from serum-free medium under free floating conditions [40][41][42] . In brief, ES cell colonies formed on MEF feeder layers at clonal density are mechanically picked.…”
Section: Differentiation Of Es Cells By the Neural Stem Sphere Methodsmentioning
confidence: 99%
“…In our method, astrocytes derived from ES cells in a chemically de fi ned medium can be used for continuous generation of neurons [ 38 ] (Fig. 15.2 ).…”
Section: Es Cells As Donor Cellsmentioning
confidence: 99%
“…24 Human neurons, generated from ESCs by the NSS method, have been shown to survive in murine brains following xenotransplantation. 34 Nakayama and colleagues 29 reported that the NSS method was very efficient because each ESC generated 1000 NSCs in an 11-day period. Moreover, serumfree induction is possible because chemically defined N-2 medium can generate NSS without having to resort to rodent ACM.…”
mentioning
confidence: 99%
“…Moreover, serumfree induction is possible because chemically defined N-2 medium can generate NSS without having to resort to rodent ACM. 34 We hypothesized that the NSS method could be applied to iPSC differentiation. In the present study, we transferred iPSC colonies to floating cultures, and differentiated NSCs on the surface of the NSS.…”
mentioning
confidence: 99%
See 1 more Smart Citation